New information about the pre-imaginal morphology of genus Graptomyza (Diptera, Syrphidae, Volucellini): description of third-instar larva and re-description of puparium of G. signata (Walker, 1860) - Andrea Aracil (African Invertebrates, 2019)
Pre-imaginal morphology of the flower fly species Graptomyza signata (Walker) is described and figured in detail based on specimens collected on a decomposed Aloe-like plant in KwaZulu-Natal province, South Africa. Third-instar larva is described for the first time and the puparium morphology is re-described using both light (optical) and electron microscopy. The present work represents the second larval description for a species of the genus Graptomyza, after the description of the larva of G. alabeta Séguy. The immatures of these two Graptomyza species were examined and compared to the pre-imaginal stages of the other members of the tribe Volucellini, pointing out the possible diagnostic characters of the genus Graptomyza. Moreover, new DNA barcodes are provided for G. signata and deposited in the NCBI GenBank.